It is the lymph node ratio that determines survival and recurrence patterns in resected distal cholangiocarcinoma. A multicenter international study. Issue 7 (July 2022) - Di Martino, Marcello; Koh, Ye Xin; Syn, Nicholas; Min Chin, Ken; Fernando Burdió,; Sánchez Velázquez, Patricia; Manzoni, Alberto; Benedetti Cacciaguerra, Andrea; Prieto, Mikel; Lancellotti, Francesco; Malleo, Giuseppe; Marchegiani, Giovanni; et al.
Abstract: Background: Distal cholangiocarcinoma (dCC) is still associated with a poor overall survival (OS). This study aims to investigate the impact of novel prognostic scores in comparison with more traditional ones. Methods: Multicentric retrospective analysis of patients who underwent a pancreatoduodenectomy (PD) for dCC. An unadjusted analysis was used to identify predictors of decreased survival. Significant variables were introduced in a multivariable model that assessed OS, recurrence-free survival (RFS), early recurrence (defined as a recurrence within the first 12 months from the PD), local and distant recurrence. Prognostic scores evaluated included the TNM staging system, the lymph-node ratio (LNR), the platelet-lymphocyte ratio (PLR), the neutrophil-lymphocyte ratio (NLR) and the systemic inflammation index (SII). Results: The study included 232 patients with resected dCC. The optimal cut-off value for LNR was 15% (LNR15). On the unadjusted analysis T stage (p = 0.012), N stage (p < 0.001), LNR15 (p < 0.001), grade (p < 0.001), perineural invasion (p < 0.001) and the R1 status of resection margin (p = 0.001) accounted for the decreased OS. No significant association between survival and PLR, NLR and SII were found. On the multivariable analysis only LNR15, perineural invasion and R1 were independent predictors of decreased RFS (p = 0.003, p = 0.021 and p = 0.009, respectively) and OS (p = 0.001, p = 0.016 and p = 0.013, respectively). Additionally, LNR15 was an independent predictor of early recurrence (p = 0.003) and both LNR15 and R1 were associated with increased local (p < 0.001 and p = 0.010) and distant recurrence (p < 0.001 and p = 0.003). Conclusions: LNR15 is an independent predictor of DFS, OS, early, local and distal recurrence, combined with the status of the resection margin and perineural invasion.